2019
DOI: 10.1364/optica.6.000347
|View full text |Cite
|
Sign up to set email alerts
|

Resolution-enhanced quantum imaging by centroid estimation of biphotons

Abstract: The spatial resolution of an optical system is limited by diffraction. Various schemes have been proposed to achieve resolution enhancement by employing either a scanning source/detector configuration or a two-photon response of the object. Here, we experimentally demonstrate a full-field resolution-enhancing scheme, based on the centroid estimation of spatially quantum-correlated biphotons. Our standard-quantum-limited scheme is able to image a general non-fluorescing object, using low-energy and low-intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 44 publications
0
62
0
Order By: Relevance
“…Furthermore, a demonstration of the quantum illumination protocol in which thermal light, as opposed to a coherent state, is used as the incoming parasitic light so as to better represent environmental light statistics would be a demonstration of the potential real-world applications of the quantum illumination protocol.In quantum imaging, commonly used properties are spatial quantum-correlations, which can be exploited to surpass the classical limits of imaging [12,13,14,15,16]. These quantum-correlations have been used in the case of NOON states for enhanced phase detection [17,18], through the use of definite number of photons, to improve the signal to noise ratio for measuring the absorption of objects through sub-shot-noise measurements [15,19,20,21], and to perform resolution-enhanced imaging by centroid estimation of photon-pairs [22]. Such schemes rely on the ability to detect and utilise quantum proprieties after the probed object, and are therefore sensitive to decoherence through the introduction of environmental noise and optical losses that lead to severe degradation of the quantum enhancement [23].…”
mentioning
confidence: 99%
“…Furthermore, a demonstration of the quantum illumination protocol in which thermal light, as opposed to a coherent state, is used as the incoming parasitic light so as to better represent environmental light statistics would be a demonstration of the potential real-world applications of the quantum illumination protocol.In quantum imaging, commonly used properties are spatial quantum-correlations, which can be exploited to surpass the classical limits of imaging [12,13,14,15,16]. These quantum-correlations have been used in the case of NOON states for enhanced phase detection [17,18], through the use of definite number of photons, to improve the signal to noise ratio for measuring the absorption of objects through sub-shot-noise measurements [15,19,20,21], and to perform resolution-enhanced imaging by centroid estimation of photon-pairs [22]. Such schemes rely on the ability to detect and utilise quantum proprieties after the probed object, and are therefore sensitive to decoherence through the introduction of environmental noise and optical losses that lead to severe degradation of the quantum enhancement [23].…”
mentioning
confidence: 99%
“…The developments that are currently ongoing have the potential to bring efficient imaging techniques and sensors to new domains of optics. Further to the potential applications of quantum imaging schemes, it has been demonstrated that imaging schemes at conventional wavelengths can be improved by using quantum sources, either by enhancing the resolution or decreasing the noise of images [141,52]. Future developments in quantum imaging could come through new approaches such as quantum image processing [191] or through exploiting quantum correlations via different methods such as correlation plenoptic imaging [192].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of full field imaging of non fluorescing objects (that is, without scanning), states exhibiting quantum correlated illumination can be used to gain a resolution improvement [132]. Recently, we have demonstrated a resolution enhancement in full-field imaging under of non fluo-rescing objects [141] using a centroid measurement detection method for bi-photons [142].…”
Section: Superresolution In Quantum Imagingmentioning
confidence: 99%
“…The governing law for this process is momentum conservation that ensures correlations between the photons in the pair 19,20 . These correlations can be exploited for ghost imaging [21][22][23] , imaging Bell-type non-local behaviour 24 , imaging at enhanced spatial resolution 25,26 , quantum-enhanced target detection 27 and to distil an image encoded in quantum states in the presence of classical background radiation 28,29 . We note that recently, Ianzano et al 30 have demonstrated the measurement of polarisation entanglement using a camera, owing to its high-temporal resolution (1.5 ns).…”
Section: Introductionmentioning
confidence: 99%